143 Effects of Increasing Dietary Standardized Ileal Digestible Lysine Levels on Growth Performance of 13- to 23-Kg Pigs Sired by PIC 800 Boars. (12th April 2022) - Xue, Pengcheng; Lu, Ning; Pilcher, Chad M; Frederick, Brent; McGhee, Molly L; Li, Qingyun; Vier, Carine M; Cast, Wayne R; Orlando, Uislei A
Abstract: An experiment was conducted to determine the effects of increasing dietary standardized ileal digestible (SID) Lys on growth performance of late nursery pigs. A total of 546 pigs (PIC 800 × Camborough, initially 12.6 ± 0.56 kg) were used in a 21-d trial. Pens of pigs were weighed, blocked by body weight, and randomly allotted to 1 of 6 treatments that contained 1.10, 1.16, 1.23, 1.29, 1.39, or 1.49% SID Lys (corresponding to 85.0, 90.0, 95.0, 100.0, 107.5, or 115.0% of PIC SID Lys recommendations). Diets were corn-soybean meal-based and contained 2, 450 kcal/kg net energy (NE). There were 7 pens/treatment and 13 pigs/pen (6 or 7 gilts and 7 or 6 barrows, balanced among treatments). Data were analyzed using generalized linear and nonlinear mixed models with pen as the experimental unit. Competing models included linear, quadratic polynomial, broken-line linear (BLL), and broken-line quadratic (BLQ). Increasing SID Lys concentration increased average daily gain (ADG; quadratic, P = 0.05) and gain to feed ratio (G:F; linear, P < 0.05; Table 1). Although the best fitting model for G:F was linear, the greatest improvement in efficiency was observed as SID Lys increased from 1.10 to 1.23%. The best-fitting models for ADG were BLL and BLQ. The BLL and BLQ models estimated the breakpoint of SID Lys at 1.26% (95.4% of PIC SID Lys recommendation; 95% CI: 1.17 to 1.29%) and 1.23% (95.0% of PIC SID Lys recommendation; 95% CI: 1.18 to 1.28%), respectively. There was no evidence that increasing dietary SID Lys levels impacted average daily feed intake or the removal and mortality rate. In the current trial with dietary NE at 2, 450 kcal/kg, the estimated optimum SID Lys concentration for 13 – 23 kg pigs sired by PIC 800 boars ranged from 1.23 to 1.26%, depending on the statistical model.